PERFORMANCE EVALUATION OF ADVANCED TRAFFIC CONTROL SYSTEMS AT SIGNALISED INTERSECTIONS FAR FROM ADJACENT INTERSECTIONS - A. Caroline Sutandi (Institute of Research and Community Outreach - Petra Christian University, 2007)
Advanced Traffic Control Systems (ATCS) have been recognised as one of the most direct methods for relieving urban traffic congestion. However, the applications of the systems in large cities in developing countries are unique because road networks in these cities face more severe transportation problems than those in developed countries. Furthermore, some of signalised intersections lie close, but others far from adjacent intersections. The aim of this paper is to evaluate the performance of ATCS at intersections with far distance to adjacent intersections and to recommend how to improve traffic performance with given constraints of severe transportation problems. Road network in Bandung, Indonesia was used as a case study. Microscopic traffic simulation was conducted to evaluate the performance of ATCS. It is shown that on average, traffic performance measures under Fixed Time traffic control system were similar or better than those under ATCS. In conclusion, the application of ATCS at intersections far from adjacent intersections is not effective.